Introducing a New Lexicographical Model: AlphaConceptual+ (and How it Could Be Applied to Dictionaries for Luganda) - Kawalya, Deo; de Schryver, Gilles-Maurice (Lexikos, 2013)
In this article we explore the possibility of amalgamating the semasiological (i.e. alphabetical), onomasiological (i.e. conceptual) and visual approaches to dictionary compilation, here termed an alphaconceptual+ (i.e. alphaconceptual 'plus') dictionary, using Luganda as a brief case study. Such a dictionary would combine the strong points of alphabetical and conceptual lexicography, with all entries also linked to relevant picture plates. In Section 1 we expound on the history of Luganda lexicography, highlighting the different types of dictionaries in the language since the early 1900s. Section 2 is an exposition of semasiological and onomasiological lexicography. In Sections 3 and 4 we study the actual dictionary market and scholarly lexicographic literature, in Africa and the rest of the world respectively. In Section 5 a case for language-independent alphaconceptual+ lexicography is argued, and its proposed compilation approach is sketched out in Section 6, followed by the conclusion in Section 7.